Effect of the amount of nickel sulphide, molybdenum disulphide and carbon nanosupport on a Tafel slope and overpotential optimization. (4th May 2017) - Sarno, Maria; Ponticorvo, Eleonora
Abstract: A Tafel slope of 40 mV dec −1 and a very small overpotential were measured for our NiSMoS2 G nanocatalyst, prepared using a scalable approach, and consisting of NiS nanoparticles covered by a stabilizing coating of MoS2 nanosheets, on unsophisticated and easy to obtain physical exfoliated graphite. A careful study proves that it is possible to improve the Tafel slope and the overpotential through the optimization of amounts of the different components. The conductive nanocarbon network, the highly active to charge accumulation of NiS nanoparticles and the coupling with MoS2 nanosheets, exposing a large number of edges, result in a very high hydrogen production rate of 1.63 ml cm −2 h −1 at −0.12 V, measured by means of an on-line mass spectrometry analysis.